Temperament and Self-Harm Behavior in University Students - Noor, Nimra; Irfan, Sadia (Applied Psychology Review, 2023)
The current study aimed to investigate the relationship between temperament and self-harm behavior in university students. This was a correlational study in which a total of 300 university students were involved ranging from 19 to 23 years (M ₌ 21.04, SD ₌ 1.26). Two self-report measures were used including the Temperament Scale for University Students (TSUS) and Self-Harm Tendencies Scale (SHTS). The results concluded that impulsivity, submissiveness, and introversion temperament traits were positively linked with self-harm behavior and only apprehensiveness temperament predicted self-harm behavior. Overall, women were found to be more prone to self-injurious behaviors.